Inclusive physical activity games at school: The role of teachers’ attitude toward inclusion - Gentile, Ambra; Giustino, Valerio; Rodriguez-Ferrán, Olga; La Marca, Alessandra; Compagno, Giuseppa; Bianco, Antonino; Battaglia, Giuseppe; Alesi, Marianna (Frontiers in Psychology, 2023)
Introduction Inclusive physical activity games at school can be useful for teachers dealing with students with disabilities. The use of inclusive strategies and games can be directly linked to teachers’ self-efficacy and familiarity with the inclusive strategies, while it could be indirectly influenced by their attitude toward inclusion and, in a smaller part, by social desirability in their response. Moreover, teachers’ responses could be different among the different school grades. Therefore, the aim of the current study is to investigate the role of attitude toward inclusion, social desirability, self-efficacy, and familiarity in the use of physical activity games at school in teachers from all school grades. Methods A sample of 1,583 schoolteachers was asked to fill out a questionnaire about their perceptions of governmental measures, self-efficacy, familiarity with inclusive strategies through physical activity, and two standardized questionnaires assessing attitudes toward inclusion and social desirability. Results Teachers from primary school reported lower scores in attitude toward inclusion total score and dimensions, namely impact on teacher, impact on the environment, impact on the other children, and impact on the student with disability. Moreover, the path analysis model showed that the attitude toward inclusion indirectly influenced the use of inclusive strategy and had a small direct effect on familiarity with inclusive strategies and self-efficacy. Social desirability slightly influenced both familiarity and self-efficacy but not the use of inclusive strategies. Familiarity and self-efficacy had a direct effect on the use of inclusive physical activity games. Discussion The results of the current study suggest that being familiar with and having a high self-efficacy in implementing inclusive strategies are well related to the use of inclusive strategies at school. In addition, more attention should be given to kindergarten and primary school teachers, who reported lower scores in the attitude toward inclusion and higher scores in social desirability.